Effectiveness of social media usage in politics / Muhammad Akmal Azizi Othman and Mohd Afiq Mat Zainuddin - Othman, Muhammad Akmal Aziz; Mat Zainuddin, Mohd Afiq (2018)
Social media is an important form of communication in the world of global era nowadays. As Internet-based applications, social media allows its users to contribute and feedback openly and share information in a rapid and unrestricted. In the context of politics, social media acts as the power tools most influential. It provides a common space (public sphere) for people to disclose their political participation freely and without any pressure. Social media provide space or special area in society where each individual can interact and thus affect the free of a political action. Thus, this research studies the correlation between the effectiveness of social media in politics and good content and attractive homepage, effective campaigning tools and political discussions. The research explores the effectiveness of social media usage in the rural area in Bagan Serai, Perak. Based on overall observation, the social media has being become an important tool in political activities. The research shows on how the social media influences the youth to know about politics. The election result reflects the influence of social media in Malaysian politics.